2011
DOI: 10.2215/cjn.06020710
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria Induced by Parenteral Iron in Chronic Kidney Disease—A Comparative Randomized Controlled Trial

Abstract: SummaryBackground and objectives Among patients with chronic kidney disease (CKD), differences in proteinuria are seen between intravenous iron preparations after a single dose exposure. This study examined differences in proteinuria between two intravenous iron preparations after multiple doses.Design, setting, participants, & measurements Patients with iron-deficiency anemia and CKD, stratified by angiotensin converting enzyme inhibitor (ACEI)/angiotensin receptor-blocker (ARB) use, were randomized to iron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…Zager et al [30,31] demonstrated that parenteral iron not only induced intracellular iron accumulation, marked lipid peroxidation and cell injury in isolated mouse and human tubular epithelial cells but also showed nephrotoxicity after IV iron injection in vivo. Three small studies on patients with CKD demonstrated that short-term IV iron administration caused transient proteinuria and urinary excretion of tubular enzymes [32][33][34]. Because of the lack of data about baseline serum creatinine and proteinuria, our study results are not sufficient to demonstrate that the patients treated with iron really have a higher risk to reach dialysis.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 60%
“…Zager et al [30,31] demonstrated that parenteral iron not only induced intracellular iron accumulation, marked lipid peroxidation and cell injury in isolated mouse and human tubular epithelial cells but also showed nephrotoxicity after IV iron injection in vivo. Three small studies on patients with CKD demonstrated that short-term IV iron administration caused transient proteinuria and urinary excretion of tubular enzymes [32][33][34]. Because of the lack of data about baseline serum creatinine and proteinuria, our study results are not sufficient to demonstrate that the patients treated with iron really have a higher risk to reach dialysis.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 60%
“…Similar analyses have been performed in repeated dose studies. In a multicenter, randomized trial, 62 patients with ND-CKD and iron deficiency anemia received a weekly dose of either iron sucrose or ferric gluconate (100 mg) for 5 weeks [19]. Basal levels of proteinuria were similar, but increased post-dosing, with a greater increase with iron sucrose than ferric gluconate [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter, randomized trial, 62 patients with ND-CKD and iron deficiency anemia received a weekly dose of either iron sucrose or ferric gluconate (100 mg) for 5 weeks [19]. Basal levels of proteinuria were similar, but increased post-dosing, with a greater increase with iron sucrose than ferric gluconate [19]. This was consistent with results from an earlier single-dose study from the same group which showed that a single dose of iron sucrose (100 mg) provoked a significantly higher urinary protein to creatinine ratio than ferric gluconate [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal models have demonstrated the potential detrimental effects of free iron on glomerular function [23], as well as clinical studies by Agarwal et al [24,25]. More recent clinical data on the neutral effects of IV iron on renal function are encouraging [26].…”
Section: Discussionmentioning
confidence: 99%